Hundertwasser's theory and its relation to the Slow fashion movement (ModaPalavra e-periódico, 2020)
This article proposes to develop a relationship betweenbehavioral tendencies, the work of Hundertwasser’s artist andthe Slow fashion movement, and understand better howfashion influences personal attitudes and how it hascontributed to huge changes of the current market.Demonstrate through the behavioral analysis that eachidentity is built from the consumes and way of life.
Keywords: fashion design; trend; hundertwasser